The effect of clinically recommended Evolut sizes on anchorage forces after BASILICA. (30th March 2021) - Yaakobovich, Halit; Plitman Mayo, Romina; Zaretsky, Uri; Finkelstein, Ariel; Weiss, Dar; Marom, Gil
Abstract: Coronary artery obstruction (CAO), a fatal complication of transcatheter aortic valve replacement (TAVR), is commonly found after Valve-in-Valve implantation inside a degenerated bioprosthetic valve. Leaflet laceration (BASILICA technique) has been proposed to prevent CAO and to potentially reduce the risk of leaflet thrombosis. We have previously demonstrated that this technique can reduce the anchorage forces of the TAVR device, which may lead to future complications. In this short communication, we hypothesize that the anchorage force reduction can be minimized by implanting a TAVR with a larger diameter, if two sizes are clinically recommended. We evaluated this hypothesis by employing finite element models of the deployments of the Evolut 26 and 29 mm inside a 27 mm Mitroflow valve, with and without leaflet lacerations. The results show that a laceration substantially decreases the contact area between the Evolut stent and the Mitroflow valve. The larger Evolut has a larger contact area and stronger anchorage forces. Additionally, the anchorage forces are less sensitive to additional lacerations in the larger Evolut (29 case). The results suggest that a larger self-expending device can ensure stronger anchorage and can lower the risk of possible migration, when TAVR is performed in a lacerated bioprosthesis.